The Stimulating Effects of Imazalil and Carbendazim Fungicides on in Vitro Propagation and ex Situ conservation of the Medicinal Balkan Range-Restricted Sideritis Raeseri Boiss & Heldr. Subsp. Raeseri - Sarropoulou, Virginia; Maloupa, Eleni (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Sideritis raeseri Boiss & Heldr. subsp. raeseri, known in Greece as Mountain tea of Parnassus or Velouchi is a range restricted medicinal plant of the Balkan peninsula. Conventional propagation methods did not allow the mass production of plant material in a short period of time due to both low seed germination rate and rooting of cuttings. Therefore, the aim of this study was to establish a reliable, reproducible and efficient regeneration protocol for mass and large-scale micropropagation, germplasm and ex situ conservation of S. raeseri Boiss & Heldr. using Imazalil and Carbendazim fungicides. After 9 weeks, 2.5-10 mg/l Imazalil stimulated root length by 1 cm but diminished root number and rooting percentage. Optimum shoot number (5.58), shoot length (24.91 mm), shoot multiplication (100%), root number (20.63) and rooting (66.67%) were recorded with 0.5 mg/l kinetin (KN) + 0.05 mg/l ?-napthaleneacetic acid (NAA) (Imazalil-free). After 4 ½ weeks, 1 mg/l Carbendazim + 0.5 mg/l 6-benzyladenine (BA) yielded 5.77 shoots/explant, 16.1 mm shoot length and 100% shoot multiplication. However, Carbendazim did not result in rooting. The ex vitro survival percentage of rooted shoot-tip explants derived from Imazalil experiment was 95%. Carbendazim proved useful in shoot proliferarion and Imazalil in root elongation of S. raeseri Boiss & Heldr. subsp. raeseri micropropagation system.